"Across Time and Space, I Am Together with Many, Many Others": Digital Writing and Temporality on Chinese Social Media. (August 2022) - Zhou, Feifei; Zhou, Xiyin
Current scholarship tends to see temporality as a problem or challenge to be overcome in communication on social media (as in "context collapse" and "time collapse"). Drawing on in-depth interviews of Chinese users of a digital writing function (bullet comments) on a major video-sharing platform, we aim to expand current research and deepen understandings of temporality and digital writing. We offer a broader, more positive conceptualization of time on social media by highlighting an alternative set of time-related practices and experiences, mediated by bullet comments. Following recent studies of individuals' making and experiencing of time in media-saturated societies, our article investigates Chinese social media users' diverse time-sensitive practices and multi-dimensional temporal experiences. We outline their creative practices from the bottom up, which make use of the distinct technological design of bullet comments. Four interrelated themes in their temporal experiences are analyzed and the similarities and differences with the Deleuzian concept of "crystal of time" explained. Overall, we demonstrate the semiotic power of digital writing in facilitating new meaning-making practices, producing multi-layered mediated temporalities, and affording multisensory, enriching, bonding experiences. The significance and implications of this study for future studies are discussed, in view of the expansion of bullet comments to Chinese mainstream, commercial platforms.